Localised assets and small-firms’ technological capabilities, spatial and organizational dynamics - Cesário, M. (2013)
The main objective of the present work is to empirically show how a set of environmental variables affects the adoption of new technologies by small firms. We report the results of the application of a common questionnaire to a sample of 167 small and medium sized firms from clothes, textile and leather sectors (TCL) belonging to the following southern European areas: North (Portugal), Valencia (Spain), Macedonia (Greece) and South Italy (Italy). The following variables were considered as possible predictors: employees, type of ownership and management, supply/distribution/customers’ networks and institutional links. A binary logistic regression was computed allowing the characterisation of the process of adoption of new technologies such as: developed internally, supplier dominated and motivated by the international market.